The implementation and performance studies of wireless networks for corporate intranet and public information resource center - Liew,, Allen Than Ho. (Universiti Malaysia Sarawak, UNIMAS, 2000)
Wireless networking provides portable and mobile users with flexibility and convenience in network and information access. WLAN allow users to remain connected to a Local Area Network (LAN) while shifting from one workplace another (portable computing) or even to remain connected while in the move (mobile computing). This thesis includes two case studies on the implementation of wireless networks, namely the Wireless Metropolitan Area Network (WMAN) for a statewide corporate multimedia network in Sarawak (StateNet) and the Wireless Local Area Network (WLAN) for a Public Information Resource Centre (PIRC) in Kuching. These case studies showcase the design considerations, which provided guidelines for future implementation of the WMAN and WLAN.